2020
DOI: 10.3346/jkms.2020.35.e27
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Mortality and Prevalence Trends in Korea, 2002–2015

Abstract: Background: Evaluation of mortality and prevalence trends is important for health planning and priority decision-making in health policy. This study was performed to examine diseasespecific mortality and prevalence trends for diseases in Korea from 2002 to 2015. Methods: In this study, 206 mutually exclusive diseases and injuries were classified into 21 cause clusters, which were divided into three cause groups: 1) communicable, maternal, neonatal, and nutritional conditions; 2) non-communicable diseases (NCDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Statistics Korea annually reports the cause of death statistics, and a previous study reported the accuracy of the cause of death to be 92%. 28 Thus, this nationwide population-based study was conducted using data from a representative sample of a large number of enrolled patients in an area where HCC incidence rates are high. Furthermore, this study had a long follow-up period (up to 14 years) to evaluate the study outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics Korea annually reports the cause of death statistics, and a previous study reported the accuracy of the cause of death to be 92%. 28 Thus, this nationwide population-based study was conducted using data from a representative sample of a large number of enrolled patients in an area where HCC incidence rates are high. Furthermore, this study had a long follow-up period (up to 14 years) to evaluate the study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this cohort contained the date and the cause of death, which were determined using the national database for cause of death produced by Statistics Korea. Statistics Korea annually reports the cause of death statistics, and a previous study reported the accuracy of the cause of death to be 92% [ 28 ]. Thus, this nationwide population-based study was conducted using data from a representative sample of a large number of enrolled patients in an area where HCC incidence rates are high.…”
Section: Discussionmentioning
confidence: 99%
“…The trends in ASRs were summarized as annual percent changes (APCs) [ 7 ]. With the APC approach, the case rates were assumed to change annually at a constant percentage.…”
Section: Methodsmentioning
confidence: 99%
“…With the APC approach, the case rates were assumed to change annually at a constant percentage. The average annual percent change (AAPC), a measure of trends over a pre-specified fixed interval, was calculated by summarizing the trend over the time period as a weighted average of the APCs [ 7 ]. All-cause-specific trends for age-standardized mortality and prevalence rates were analyzed using the joinpoint regression method with the Joinpoint Regression Program version 4.9.1 (Statistical Research and Applications Branch, National Cancer Institute, Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…13 Suicide is the fourth most common cause of death in Korea, 14 and deaths through self-harm have increased from 2002 to 2015. 15 Evidence suggests that suicide in Korea is closely related to mental illness. 16 17 18 According to nationwide statistics on the causes of suicide in 2018, 19 31.6% of suicide deaths were caused by psychiatric problems.…”
Section: Introductionmentioning
confidence: 99%